Influencers of childhood over nutrition: a cross sectional study among primary school children in Kolkata, West Bengal, India - Dasgupta, Aparajita; Bhattacharyya, Aritra; Paul, Bobby; Bandyopadhyay, Lina (International Journal of Contemporary Pediatrics, 2017)
Background: Changing trends of dietary habits and lack of physical exercise force the world to face a modern era epidemic obesity which also affects our children counterpart. Childhood obesity is now a challenge of public health to combat with. Prevalence of childhood overnutrition (obesity and overweight) found to be rising in many developing countries including India in recent decades in many studies by different researchers, it is ranging from 2.9% to 14.3%, which makes our youth vulnerable to many life-threatening consequences. Methods: It was a school based cross sectional study done in primary schools of Barasat among 548 students of 3-11 years of age group. Parental perception towards child eating behaviour were assessed with the help of CEBQ questionnaire. Results: Among the total 548 students, as per BMI 38% were overweight and obese. Then hierarchical multiple logistic regression revealed that at Step one socio-demographic factors accounted for 16.9% of the variation in overnutrition status. Introducing the responses on selected life style factors in step two and CEBQ responses in final step explained an additional 9.9% and 5% of variation respectively. At all three-level model correctly predicted 62-70.3% of the dependent variables. Conclusions: The high proportion of over nourished children were found in our study, and this found to be related with parental perception about few lifestyle and child eating behaviour which calls for further research and interventional programme for this alarming topic in this age group.